VALUDASI EKONOMI EKOSISTEM MANGROVE DI DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU. - Langga Qodrina; Rasoel Hamidy; Zulkarnaini Zulkarnaini (Program Pascasarjana Universitas Riau, 2012)
This research was conducted in Teluk Pambang Village Bantan Sub District Bengkalis Region dated from July to September 2011. This study aims to value the total economicpotential value of mangrove ecosystem in Teluk Pambang Village, determine alternativepattern of utilization and management. The method used in this study was survey method. The economic value was calculated based on the total direct economic value, indirecteconomic value, option value and existence value. This study also calculated net presentvalue (NPV) for 25 years in order to get representation for economic value in future. According to the data analysis, it was found 10 species of mangroves which has economicvalue and 7 species of mangrove fauna. The total economic value for 1 acre of mangroveecosystem was IDR. 1,409,454,390.18 acre-1 y-1 with net present value (NPV) was IDR.12,793,673,903.53 acre-1 for 25 year mangrove rotation cycle. While, the percentagebetween total resources and utilization was only 0.035%. According to this research, it canbe arranged 3 alternatives for utilizations in mangrove area. The best result of the alternativeshas been made is alternative with prioritize for sustainable ecosystem. Moreover, the management scheme which can be done for this mangrove area is a model of conservationmanagement with the aim of maintaining the sustainability of environmental services.